Growth phenotypes of very low birth weight infants for prediction of neonatal outcomes from a Brazilian cohort: comparison with INTERGROWTH - Cardoso, Viviane Cunha; Grandi, Carlos; Silveira, Rita C.; Duarte, José Luiz Bandeira; Viana, Maria Cândida Ferrarez Bouzada; Ferreira, Daniela Marques de Lima Mota; Alves, José Mariano Sales; Embrizi, Laís Furlan; Gimenes, Carolina Boschi; de Mello e Silva, Nathalia Moura; Melo, Fernanda Pegoraro de Godoi; Venzon, Paulyne Stadler; et al. (Elsevier, 2023)
Objective: To assess the predictive value of selected growth phenotypes for neonatal morbidity and mortality in preterm infants < 30 weeks and to compare them with INTERGROWTH-21st (IG21). Method: Retrospective analysis of data from the Brazilian Neonatal Research Network (BNRN) database for very low birth weight (VLBW) at 20 public tertiary-care university hospitals. Outcome: the composite neonatal morbidity and mortality (CNMM) consisted of in-hospital death, oxygen use at 36 weeks, intraventricular hemorrhage grade 3 or 4, and Bell stage 2 or 3 necrotizing enterocolitis. Selected growth phenotypes: small-for-gestational-age (SGA) defined as being < 3rd (SGA3) or 10th (SGA10) percentiles of BW, and large-for-gestational-age (LGA) as being > 97th percentile of BW. Stunting as being < 3rd percentile of the length and wasting as being < 3rd percentile of BMI. Single and multiple log-binomial regression models were fitted to estimate the relative risks of CNMM, comparing them to IG21. Results: 4,072 infants were included. The adjusted relative risks of CNMM associated with selected growth phenotypes were (BNRN/IG21): 1.45 (0.92–2.31)/1.60 (1.27–2.02) for SGA; 0.90 (0.55–1.47)/1.05 (0.55–1.99) for LGA; 1.65 (1.08–2.51)/1.58 (1.28–1.96) for stunting; and 1.48 (1.02–2.17) for wasting. Agreement between the two references was variable. The growth phenotypes had good specificity (>95%) and positive predictive value (70-90%), with poor sensitivity and low negative predictive value. Conclusion: The BNRN phenotypes at birth differed markedly from the IG21 standard and showed poor accuracy in predicting adverse neonatal outcomes.
Keywords: Network; Outcome; Phenotype; Predictive values; Premature birth; Very low birth weight